MR Imaging of Central Nervous System Whipple Disease: A 15-Year Review - Black, D.F.; Aksamit, A.J.; Morris, J.M. (American Journal of Neuroradiology, 2010)
SUMMARY: CNS WD is fatal if antibiotics are not begun early, but knowledge regarding the variety of presentations on MR imaging is limited. In order to more effectively recognize this entity on MR imaging, the Mayo Clinic medical records were reviewed for subjects diagnosed with CNS WD from 1992-2006 who had also undergone MR imaging of the neuraxis. Seven subjects were identified and their imaging findings were reviewed by the authors. Four of 7 had head MR imaging findings indicative of WD. Two subjects demonstrated high T2 signal within the corticospinal tracts. CNS WD may demonstrate high T2 signal with minimal enhancement and no restricted diffusion, primarily in the midline of the midbrain, hypothalamus, and mesial temporal lobes and occasionally the corticospinal tracts. MR imaging may also be normal. Radiologists should be aware of these presentations and be prepared to mention CNS WD as a diagnostic possibility since early antibiotic therapy may significantly impact morbidity and mortality. asxsasymptomaticCNScentral nervous systemFLAIRfluid-attenuated inversion recoveryGIgastrointestinalNPnot performedPASperiodic-acid-SchiffPCRpolymerase chain reactionRxtherapyWDWhipple disease